Implementation of Problem Based Learning (PBL) Model with Teaching At The Right Level (TaRL) Approach to Improve Student Learning Outcomes in History Material of Class XD SMA Negeri 4 Palu - Syam, Ririani Ramdhani; Misnah, Misnah; Ismail, Adsul (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to improve student learning outcomes in History subjects through the application of the Problem Based Learning (PBL) learning model combined with the Teaching at The Right Level (TaRL) approach. The study was conducted in class XD of SMA Negeri 4 Palu in the even semester of the 2024/2025 academic year with 30 students, consisting of 10 male students and 20 female students. The method used was Classroom Action Research (CAR) which was carried out in two cycles, each consisting of planning, implementation, observation and reflection stages. The results of the observation showed that the majority of students had low interest and learning outcomes. After the application of the PBL model and the TaRL approach, there was a significant increase in learning outcomes. The average student score from 68.4 in the pre-cycle to 74.2 in cycle 1 and reached 81.6 in cycle II. The percentage of learning completion from 33.3% increased to 90%. The results of the study show that the application of the PBL model with the TaRL approach is able to create an active, collaborative and participatory learning atmosphere, and help students understand historical material according to their respective ability levels.